Telerehabilitation System in Nursing Post Stroke - A Systematic Review - Dimas Hadi Prayoga; Bernadetta Germia Aridamayanti; Ida Trisnawati; Maria Fransiska Ronalia (Jurnal Ners, 2019)
Background: Stroke is currently the main cause of disability worldwide. Telerehabilitation is a rehabilitation approach that can be used to repair the damage to motor, sensory and cognitive functions. This can also substantially reduce the travel time for the health workers and therefore increase the number of patients who are consulted in a day.Method: A search using specific keywords was done in both the journal articles and in the database. In total, 119 articles were from Scopus, 45 articles were from PubMed, 87 articles were from Science Direct, 52 articles were from EBSCO and 97 articles were from Proquest. There were 15 articles that matched the inclusion criteria. Most of the available literature only refers to short-term results and most of the research is of low quality.Result: Evidence of the relative effectiveness was found in the types of videos, VR, cellphones and computer use. The location of the network support and technological progress are still obstacles that must be addressed immediately. Based on the current scientific evidence, only a few telerehabilitation methods can be recommended for wider use.Conclusion: The telerehabilitation system can provide long-term therapy, meet the patient needs and save the health resources needed to minimize the severity of the patients’ condition. The application of telerehabilitation is used by the nurses to optimize their role in improving patient health and telerehabilitation will answer the problem of penetrating the distance dimension.